2021
DOI: 10.7554/elife.65532
|View full text |Cite
|
Sign up to set email alerts
|

Genomic basis for drought resistance in European beech forests threatened by climate change

Abstract: In the course of global climate change, central Europe is experiencing more frequent and prolonged periods of drought. The drought years 2018 and 2019 affected European beeches (Fagus sylvatica L.) differently: even in the same stand, drought damaged trees neighboured healthy trees, suggesting that the genotype rather than the environment was responsible for this conspicuous pattern. We used this natural experiment to study the genomic basis of drought resistance with Pool-GWAS. Contrasting the extreme phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…This is in accordance with the study by Gričar et al (2013) , who reported that anatomical characteristics and signals of hydrological changes in Quercus robur L. xylem rings showed a strong response to micro-environmental conditions. In addition, genetics might also play a role in explaining the high variability found ( Pfenninger et al, 2021 ). We cannot exclude the possibility that such a high inter-individual variability might have obscured some patterns in alder anatomical responses to waterlogging.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the study by Gričar et al (2013) , who reported that anatomical characteristics and signals of hydrological changes in Quercus robur L. xylem rings showed a strong response to micro-environmental conditions. In addition, genetics might also play a role in explaining the high variability found ( Pfenninger et al, 2021 ). We cannot exclude the possibility that such a high inter-individual variability might have obscured some patterns in alder anatomical responses to waterlogging.…”
Section: Discussionmentioning
confidence: 99%
“…While environmental adaptations are commonly highly polygenic (Barghi et al, 2019;Hartke et al, 2021;Pfenninger et al, 2021;Rivas et al, 2018), there is increasing evidence of the effect of single gene content variation (Liu et al, 2021). For example, as has been recently…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to detect consistent changes across replicates and, therefore, to identify reliable candidates for selected SNPs, a Cochran-Mantel-Haenszel's (CMH) test was performed merging the three replicates of each experimental group. After, a BH correction for false discovery rate and a cut-off at p < 0.01 was applied (Pfenninger et al, 2021) (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Time-series Analysis Of Dna Poolseq Datamentioning
confidence: 99%